Policy and Practice: The Role of Trade Unions in Reducing Migrant Workers’ Vulnerability to Forced Labour and Human Trafficking in the Greater Mekong Subregion - Marks, Eliza; Olsen, Anna (Anti-Trafficking Review, 2015)
This paper provides an analysis of what trade unions can offer to reduce the vulnerability of migrant workers to forced labour and human trafficking in the Greater Mekong Subregion (GMS) and Malaysia as a key destination for GMS migrant workers. The exploration of the potential for the engagement of trade union partners is a timely contribution to the forced labour and anti-trafficking debate, given the shift towards a more holistic labour rights approach, and the ensuing search for more actors and partnerships to combat these crimes, which led to adoption of the Protocol of 2014 to the Forced Labour Convention, 1930, (Forced Labour Protocol) in June 2014. Examples from Malaysia and Thailand highlight the role that trade unions can play in policy development and service provision, and also some of the challenges associated with unionisation of a vulnerable, temporary, and often repressed, migrant workforce.